Glass fiber sheet for filters
The glass fiber sheet with a balanced composition of glass fibers, wood pulp, and binder addresses strength and shape followability issues, ensuring effective corrugation and functional material support.
Patent Information
- Application Number
- JP2021551641
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-07
- Filing Date
- 2020-10-05
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-10-05
AI Technical Summary
Existing glass fiber sheets face challenges in maintaining strength and shape followability during corrugation, leading to issues like uneven cell shapes and powder falling, while also struggling to effectively support functional materials.
A glass fiber sheet composed of 51 to 85% glass fibers, 10 to 49% wood pulp, and a binder content of 1 to 25% by mass, with specific fiber diameters and lengths, enhances strength and flexibility, allowing for effective corrugation and functional material support.
The glass fiber sheet exhibits excellent shape followability and prevents powder falling during corrugation, maintaining sufficient strength and effective functional material support even after processing.
Smart Images

Figure 0007619272000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass fiber sheet for filters, and more particularly to a glass fiber sheet for filters that is used as a filter by carrying a functional material therein. [Background technology]
[0002] Ceramic fibers have characteristics such as high heat resistance, high insulation, and non-combustibility, and therefore inorganic fiber sheets using ceramic fibers are widely used. For example, the inorganic fiber sheets are used as heat insulation materials, heat-resistant cushion materials, heat-resistant shield materials, separators, carriers for functional materials such as catalysts, etc. Also, honeycomb molded bodies obtained by corrugating inorganic fiber sheets are used as honeycomb filters for heat exchange carrying functional materials such as adsorbents, or honeycomb filters for gas adsorption.
[0003] For example, Patent Documents 1 and 2 describe a method for producing an inorganic fiber sheet, which involves preparing a raw material slurry containing ceramic fibers, an organic binder, and bark, and then papermaking the raw material slurry to produce an inorganic fiber sheet. Bark here is a type of naturally occurring clay mineral, and is hydrated magnesium silicate. Bark is used as an inorganic binder. Patent Document 2 also describes that an inorganic fiber sheet is corrugated to produce a honeycomb molded body, which is then fired, and the fired body is made to carry an adsorbent or the like to produce a gas adsorption element (honeycomb filter).
[0004] However, ceramic fibers are classified as Category 2 (suspected of being carcinogenic) in the EU (European Union) Directive 97 / 69EC on artificial amorphous fibers. Therefore, from the perspective of safety for the human body, deceramization is being promoted, and replacement with, for example, glass fiber or biosoluble fiber is being considered. The fiber diameter of the glass fiber used in deceramization is preferably 3 μm or more.
[0005] In light of these circumstances, for example, Patent Document 3 discloses a method for obtaining an inorganic fiber sheet by papermaking a slurry containing biosoluble ceramic fibers as the main component, glass fibers, organic fibers, a cationic inorganic binder, and sepiolite, a type of mountain bark. However, there are problems with biosoluble ceramic fibers in that it is difficult to obtain sufficient strength, and it is difficult to make them lightweight and thin.
[0006] On the other hand, glass fiber, an alternative to ceramic fiber, has a large fiber diameter and length, so inorganic fiber sheets made from it are hard and difficult to conform to shapes. As a result, it is difficult to form corrugations, and the fibers tend to break at the crests of the waves, resulting in uneven cell shapes, which creates problems when processing the corrugation.
[0007] Patent Document 4 proposes that corrugating processability can be improved by using glass fibers as the main component in combination with organic fibers having an aspect ratio of 300 to 2000. However, it was found that the bonds between the fibers of the inorganic fiber sheet are weak, and when the amount of the binder component is increased to improve this, the corrugating processability tends to be impaired. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 60-33250 [Patent Document 2] Patent No. 2925127 [Patent Document 3] Patent No. 5558518 [Patent Document 4] International Publication No. 2018 / 079529 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a glass fiber sheet for filters which has excellent shape conformability (hereinafter simply referred to as shape conformability) during corrugation even when the strength of the inorganic fiber sheet is increased, which prevents powder falling (hereinafter simply referred to as powder falling) during corrugation, and which has sufficient functional material support even after the functional material is supported. [Means for solving the problem]
[0010] The present invention has the following configuration. (1) A glass fiber sheet for a filter, which is mainly composed of glass fiber, further contains wood pulp and a binder, and is formed by wet papermaking, The glass fiber sheet for a filter functions as a filter by carrying a functional material therein, 51 to 85 mass % of the total fiber content of the glass fiber sheet for filters is the glass fiber, 10 to 49 mass% of the total fiber content of the glass fiber sheet for filters is the wood pulp, The content of the binder is 1% by mass or more based on the total mass of the glass fiber sheet for filters, The glass fiber sheet for filters has a basis weight of 15 to 55 g / m 2 A glass fiber sheet for filters. (2) The glass fiber sheet for filters according to (1), wherein the wood pulp has a beating degree of 300 to 750 CSF. (3) The glass fiber sheet for filters according to (1) or (2), wherein the weighted average fiber diameter of the glass fibers is 4 to 10 μm. (4) The glass fiber sheet for filters according to any one of (1) to (3), wherein the content of the binder is 25 mass % or less based on the total mass of the glass fiber sheet for filters. (5) The glass fiber sheet for filters according to any one of (1) to (4), wherein the binder contains polyvinyl alcohol. Effect of the Invention
[0011] According to the present invention, it is possible to provide a fiber sheet for filters that has excellent shape conformability even when the strength of the inorganic fiber sheet is increased. Also, according to the present invention, it is possible to provide a glass fiber sheet for filters that prevents powder falling during corrugation processing and has sufficient functional material support even after the functional material is supported. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Glass fiber sheet for filters> First, an example of the configuration of a glass fiber sheet for filters (hereinafter, simply referred to as a glass fiber sheet) according to one embodiment of the present invention will be described. The glass fiber sheet for filters of this embodiment contains glass fiber as a main component, and wood pulp and a binder as subcomponents, with 51-85% by mass of the total fiber content of the glass fiber sheet for filters being glass fiber, and 10-49% by mass of the total fiber content being wood pulp. The content of the binder is 1% by mass or more based on the total mass of the glass fiber sheet for filters.
[0013] The basis weight of the glass fiber sheet of this embodiment is 15 to 55 g / m 2 When the basis weight is equal to or more than the lower limit of the above range, the strength of the glass fiber sheet and the glass fiber sheet molded article obtained from the glass fiber sheet can be sufficiently obtained, and when the basis weight is equal to or less than the upper limit of the above range, the thickness can be suppressed and corrugation processing can be easily performed.
[0014] (Glass fiber) The type of glass fiber is not particularly limited, and in addition to E-glass, which is widely produced, high-strength S-glass, C-glass, which has excellent acid resistance, etc. can be used. From the viewpoint of cost, it is preferable to use inexpensive E-glass. In addition, the glass fiber may be used alone or in combination of two or more types.
[0015] The fiber length of the glass fiber is not particularly limited, but the length-weighted average fiber length is preferably 1 to 15 mm, and more preferably 1 to 10 mm. When the length-weighted average fiber length is equal to or greater than the lower limit of the above range, the strength of the resulting glass fiber sheet tends to be superior, and when the length is equal to or less than the upper limit of the above range, the texture of the resulting glass fiber sheet tends to be superior. The length-weighted average fiber length is calculated by measuring the fiber lengths of 100 fibers by microscopic observation.
[0016] The weighted average fiber diameter of the glass fiber is preferably 3 μm or more, more preferably 4 μm or more. If the weighted average fiber diameter is equal to or greater than the lower limit of the above range, it does not fall under the category of "WHO respirable fiber" and is safe for the human body. This "WHO respirable fiber" refers to a fibrous material defined by the World Health Organization (WHO) that is inhaled into the body by breathing and reaches the lungs, and has a length of more than 5 μm, a diameter of less than 3 μm, and an aspect ratio of more than 3.
[0017] The weighted average fiber diameter of the glass fiber is preferably 10 μm or less, more preferably 7 μm or less. If it is equal to or less than the upper limit of the above range, the strength of the glass fiber sheet and the strength of the filter substrate obtained by firing the glass fiber sheet are both improved. The weighted average fiber diameter is calculated by measuring the fiber diameters of 100 fibers by microscopic observation.
[0018] The glass fiber content of the glass fiber sheet is 51 to 85% by mass. The glass fiber content is preferably 55% by mass or more, and more preferably 58% by mass or more, based on the total mass of the fibers contained in the glass fiber sheet. The glass fiber content is preferably 80% by mass or less, and more preferably 68% by mass or less, based on the total mass of the fibers contained in the glass fiber sheet.
[0019] (Wood pulp) As the wood pulp, coniferous pulp and hardwood pulp can be used. As the wood pulp, for example, NBKP, LBKP, NBSP, LBSP, GP, etc. can be mentioned, and the pulping method is not particularly limited. Among them, NBKP is preferable because of its excellent strength.
[0020] The wood pulp content in the glass fiber sheet is 10 to 49% by mass of the total fiber content. The wood pulp content is preferably 20% by mass or more, and more preferably 32% by mass or more, based on the total mass of the fibers contained in the glass fiber sheet. The wood pulp content is preferably 45% by mass or less, and more preferably 42% by mass or less, based on the total mass of the fibers contained in the glass fiber sheet.
[0021] Wood pulp has superior flexibility compared to other organic fibers, so that even if the amount of binder is increased, problems during corrugation processing (such as shape conformity) can be solved. The degree of beating of wood pulp is preferably 300 to 750 CSF, more preferably 450 to 750 CSF. Beating is performed using a beater or the like, and within the above range of degree of beating, the flexibility of the glass fiber sheet can be increased due to its softness, and the strength of the glass fiber sheet can be increased by entangling the fibrillated parts of the pulp with the glass fibers. Furthermore, the impregnated functional material, etc. adheres to the fibrillated parts of the pulp present inside the glass fiber sheet, so that the functional material, etc. can be efficiently supported.
[0022] (Organic Fiber) In the glass fiber sheet for filters of this embodiment, wood pulp is used as a secondary component, but other organic fibers may be used in combination therewith within a range that does not impair the effect of using the wood pulp.
[0023] Examples of organic fibers include natural fibers and synthetic fibers. Examples of natural fibers include natural fibers such as cotton, wool, silk, and hemp. There are no particular limitations on the synthetic fibers, so long as they do not melt when heated during the manufacturing process of the glass fiber sheet, and they can be appropriately selected depending on the drying temperature set in the manufacturing process of the glass fiber sheet. Examples of synthetic fibers include chemical fibers such as polyethylene fibers, polypropylene fibers, polybutene fibers, nylon fibers, rayon fibers, cupra fibers, acetate fibers, polyvinyl chloride fibers, acrylic fibers, polyester fibers, polyurethane fibers, polyparaphenylene benzobisoxazole fibers, polyamideimide fibers, polyimide fibers, polyarylate fibers, polyetherimide fibers, vinylon fibers, polycarbonate fibers, ethylene-vinyl acetate fibers, ethylene vinyl alcohol fibers, polyphenylene sulfide fibers, polyethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, and aramid fibers. Any one or more of these may be used in combination.
[0024] The length-weighted average fiber length of the organic fibers that can be used in combination is preferably 1 to 15 mm, more preferably 1 to 10 mm. If the length-weighted average fiber length is equal to or greater than the lower limit of the above range, the yield during papermaking tends to improve, while if it is equal to or less than the upper limit of the above range, the organic fibers tend to be less likely to become entangled and form lumps. The length-weighted average fiber length is calculated by measuring the fiber lengths of 100 fibers by microscopic observation.
[0025] The weighted average fiber diameter of the organic fiber that can be used in combination is not particularly limited, but is preferably 3 times or less, more preferably 2 times or less, the weighted average fiber diameter of the glass fiber. When the weighted average fiber diameter of the organic fiber is 3 times or less than the weighted average fiber diameter of the glass fiber, the effect of reducing the rigidity of the glass fiber sheet and the effect of improving the folding strength by the organic fiber tend to be improved. In particular, since the weighted average fiber diameter of the glass fiber is preferably 3 to 10 μm, the weighted average fiber diameter of the organic fiber is preferably 30 μm or less, more preferably 20 μm or less. The lower limit of the weighted average fiber diameter of the organic fiber is not particularly limited, but is preferably 1 μm or more, more preferably 3 μm or more. Organic fibers having a weighted average fiber diameter of the above lower limit or more are relatively easy to obtain, so it is preferable. The weighted average fiber diameter of the fiber diameter is calculated by measuring the fiber diameter of 100 fibers by microscopic observation. When the cross-sectional shape of the organic fiber is flat, the short diameter and the long diameter are measured to calculate the cross-sectional area, and the diameter of a circle equivalent to the cross-sectional area is defined as the fiber diameter.
[0026] (binder) As the binder, an organic binder component or an inorganic binder component can be used. The content of the binder is 1% by mass or more based on the total mass of the glass fiber sheet for filters. The content of the binder is preferably the content of the binder added in the manufacturing process of the glass fiber sheet for filters.
[0027] The organic binder component is a component that bonds fibers together. Examples of the organic binder component include thermoplastic resins that are at least partially melted by heating when producing a glass fiber sheet, and can be appropriately selected depending on the drying temperature when producing the glass fiber sheet. There is no limitation on the form of the organic binder component, and it may be any of fibrous, particulate, emulsion, liquid, etc.
[0028] Examples of thermoplastic resins include polyethylene resins, vinyl chloride resins, (meth)acrylic ester resins, styrene-acrylic ester copolymers, vinyl acetate resins, vinyl acetate-(meth)acrylic ester copolymers, ethylene-vinyl acetate copolymers, polyester resins, polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymers, etc. Also, rubber emulsions such as styrene-butadiene rubber (SBR) and nitrile rubber (NBR) may be used. One or more of these may be used as the thermoplastic resin.
[0029] The organic binder component may be a composite fiber in which two or more materials with different melting points are combined, and the lower melting point part melts and acts as a binder. Examples of the composite fiber include core-sheath fibers and side-by-side fibers. Examples of the core-sheath fibers include fibers in which a low melting point sheath made of polyethylene or the like is formed around a high melting point core made of polyethylene terephthalate, polypropylene, or the like.
[0030] As the organic binder component, a thermosetting resin that hardens by heating during the manufacturing process of the glass fiber sheet to bond the fibers together can also be used. Examples of the thermosetting resin include phenolic resin, epoxy resin, melamine resin, urea resin, unsaturated polyester resin, polyurethane resin, and thermosetting polyimide resin. One or more types of thermosetting resin can be used.
[0031] Among them, it is preferable to use polyvinyl alcohol (PVA fiber, etc.) as the organic binder component because of its excellent adhesive strength. In addition, when the glass fiber sheet is required to have improved water resistance, it is also preferable to use an acrylic resin emulsion, etc. The use of these organic binder components is preferable because it improves the strength of the glass fiber sheet and suppresses powder fall of the obtained glass fiber sheet molding.
[0032] The content of the organic binder component in the glass fiber sheet is 1% by mass or more, preferably 1 to 25% by mass, and more preferably 3 to 20% by mass, based on the total mass of the glass fiber sheet. The content of the organic binder component is preferably the content of the binder added in the manufacturing process of the glass fiber sheet for filters. When the content of the organic binder component is equal to or more than the lower limit of the above range, the fibers can be sufficiently bonded to each other. When the content is equal to or less than the upper limit of the above range, when the glass fiber sheet is fired to form a filter substrate, the amount of the organic binder component that is burned off during firing is small, and the voids between the fibers that are formed due to such burning off can be reduced, which is preferable.
[0033] When polyvinyl alcohol is used as the organic binder component, the content of polyvinyl alcohol relative to the total mass of the organic binder component is preferably 20% by mass or more, and more preferably 40% by mass or more. The content of polyvinyl alcohol relative to the total mass of the organic binder component may be 100% by mass. When an acrylic resin emulsion is used as the organic binder component, the content of acrylic resin (solid content) relative to the total mass of the organic binder component is preferably 5 to 70% by mass.
[0034] The inorganic binder component is not particularly limited, and examples thereof include colloidal silica, water glass, calcium silicate, silica sol, alumina sol, sepiolite, and alkoxysilane. One or more of these can be used as the inorganic binder component. However, these inorganic binders may fall off when subjected to external forces such as rubbing and bending, and may have poor handleability. Therefore, the content of the inorganic binder component is preferably 10% by mass or less, more preferably 7% by mass or less, based on the total mass of the glass fiber sheet.
[0035] (Other Ingredients) The glass fiber sheet of the present embodiment may contain, in addition to the glass fiber and wood pulp that are the main fibers described above, and a binder, one or more inorganic fibers other than the glass fibers, and one or more optional components that are added when the glass fiber sheet is produced by wet papermaking, within a range that does not impair the effects of the present invention.
[0036] The inorganic fibers other than glass fibers are not particularly limited, but in consideration of safety to the human body, biosoluble inorganic fibers are preferable.
[0037] In this specification, the biosoluble inorganic fiber is a fiber that does not fall under the category of "WHO respirable fiber" as described above, or a fiber that satisfies any one of the following four conditions (1) to (4) according to the NotaQ "Criteria for Biosoluble Fibers" of EU Directive 97 / 69 / EC. Biosoluble inorganic fibers include biosoluble ceramics, biosoluble rock wool, etc.
[0038] The four conditions are as follows: (1) In short-term inhalation exposure animal experiments, the half-life of fibers longer than 20 μm is less than 10 days. (2) In short-term intratracheal instillation animal experiments, the half-life of fibers longer than 20 μm is less than 40 days. (3) There is no significant carcinogenicity in animal experiments using intraperitoneal administration. (4) In long-term inhalation exposure animal experiments, no pathological findings or tumor formation associated with carcinogenicity were observed (however, the composition of the substance contains alkali and alkaline earth oxides (Na 2 OK 2 O, CaO, MgO, BaO) in excess of 18% by mass.
[0039] Biosoluble inorganic fibers usually contain non-fibrous "shot" due to their manufacturing process, but if biosoluble inorganic fibers with a high shot content are used, the resulting glass fiber sheet may have problems such as holes and powder falling. Therefore, it is preferable to use biosoluble inorganic fibers with a shot content of 20 mass% or less. In addition, the biosoluble inorganic fibers may be used alone or in combination of two or more types.
[0040] From the viewpoint of safety for the human body, the glass fiber sheet of the present embodiment preferably does not contain ceramic fibers classified as category 2 (suspected of being carcinogenic) in EU Directive 97 / 69EC. The proportion of inorganic fibers other than glass fibers in the glass fiber sheet is preferably 45 mass % or less, more preferably 30 mass % or less, based on the total mass of the glass fiber sheet.
[0041] The glass fiber sheet is formed by wet papermaking, and optional components to be added at that time are not particularly limited. Examples of optional components include auxiliaries, additives, and fillers.
[0042] Examples of the auxiliary include crosslinking agents such as epoxy, isocyanate, carbodiimide, and oxazoline crosslinking agents, and silane coupling agents having functional groups such as amino, epoxy, methacryloxy, acryloxy, and mercapto groups, and one or more of these can be used. The content of the silane coupling agent is preferably 10 parts by mass or less relative to 100 parts by mass of the binder.
[0043] Examples of additives include antioxidants, light stabilizers, UV absorbers, thickeners, nucleating agents, neutralizing agents, lubricants, antiblocking agents, dispersants, flow improvers, release agents, flame retardants, foaming agents, colorants, wetting agents, tackifiers, retention improvers, paper strength improvers, drainage agents, pH adjusters, defoamers, preservatives, pitch control agents, etc., and one or more of these can be used. The content of the additives is preferably 5% by mass or less based on the total mass of the glass fiber sheet.
[0044] Examples of the filler include calcium silicate, calcium carbonate, kaolin, talc, plastic pigments, glass beads, hollow glass beads, etc., and one or more of these can be used.
[0045] (Method of manufacturing glass fiber sheets for filters) Next, an example of a method for producing a glass fiber sheet for filters according to the present embodiment will be described. In the method for producing a glass fiber sheet for filters according to the present embodiment, a raw material slurry containing the above-mentioned glass fibers, wood pulp and binder is wet-laid to produce a glass fiber sheet.
[0046] The raw material slurry used for producing the glass fiber sheet contains glass fibers as the main fiber, wood pulp and a binder. The raw material slurry may also contain a filler as an optional component. The slurry usually contains water as a slurry medium.
[0047] Wet papermaking can be carried out by preparing a raw material slurry containing the above-mentioned components and water (medium), and then making the raw material slurry into paper using a known papermaking machine. Examples of papermaking machines include cylinder papermaking machines, inclined papermaking machines, Fourdrinier papermaking machines, and short wire papermaking machines, and multi-layer papermaking can be carried out using the same or different types of papermaking machines in combination. However, a single-layer sheet is preferable for corrugation processing. Note that in the case of a multi-layer sheet, since interlayer peeling is likely to occur during corrugation processing, it is necessary to increase the amount of wood pulp and binder.
[0048] There is no particular limitation on the method of dehydration and drying after papermaking, and for example, known dryers such as Yankee dryers, cylinder dryers, air dryers, infrared dryers, etc. There is no particular limitation on the drying temperature, but it is usually about 100°C to 200°C.
[0049] The organic binder component or the inorganic binder component may be added to the raw material slurry for producing the glass fiber sheet, but a liquid containing the organic binder component or the inorganic binder component may be attached (external application) to the obtained glass fiber sheet by a method such as spray application, curtain application, impregnation application, bar application, roll application, blade application, etc. The nonwoven fabric to be externally applied may be a dried nonwoven fabric after drying or a wet web before drying.
[0050] <Corrugated processing> The glass fiber sheet for filters of the present embodiment may be corrugated into a honeycomb shape and used as a filter.
[0051] For example, a corrugated (uneven) glass fiber sheet can be obtained by corrugating the above-mentioned glass fiber sheet. A half-corrugated glass fiber sheet molded body can be obtained by bonding a corrugated glass fiber sheet (core paper) and a non-corrugated glass fiber sheet (liner). A honeycomb molded body can be produced by stacking a plurality of half-corrugated glass fiber sheet molded bodies. An adhesive may be used when laminating glass fiber sheets. Examples of the adhesive include inorganic adhesives such as colloidal silica, water glass, sepiolite, and alumina sol, and one or more of these may be used. In addition, an organic adhesive such as ethylene-vinyl alcohol may be used in combination with the adhesive.
[0052] The honeycomb formed body may be used as a filter as it is, or may be used as a filter after being fired.
[0053] <Functional Materials> The glass fiber sheet for filters of this embodiment functions as a filter by supporting a functional material inside, and therefore the glass fiber sheet for filters of this embodiment is a sheet for supporting a functional material.
[0054] Examples of functional materials include various known adsorbents and dehumidifiers. Examples of adsorbents include porous bodies such as silica gel, zeolite, sepiolite, activated carbon, and silicon oxide; catalysts such as manganese oxide, copper oxide, titanium oxide, chromium oxide, iron oxide, nickel oxide, zinc oxide, and cobalt oxide; and ion exchange resins. These may be used alone or in combination. They may also be used in the form of a composite in which the surface of a porous body is coated with a catalyst. In particular, catalysts such as titanium oxide are preferred as adsorbents for volatile organic compounds (VOCs).
[0055] Examples of dehumidifying agents include silica, zeolite, hydrophobic synthetic zeolite, natural zeolite, sepiolite, hydrotalcite, alumina, lime, gypsum, dolomite lime, magnesium hydroxide, perlite, diatomaceous earth, lithium chloride, calcium chloride, Portland cement, alumina cement, palygorskite, aluminum silicate, activated clay, activated alumina, bentonite, talc, kaolin, mica, activated carbon, and water-absorbing polymers.
[0056] Other examples of functional materials include solid adsorbents in which alkaline compounds are supported on carriers capable of adsorbing alkaline compounds (potassium carbonate, sodium carbonate, sodium bicarbonate, calcium hydroxide, calcium carbonate, etc.), activated carbon, silica, alumina, allophane, sepiolite, cordierite, and other clay minerals; sodium hydroxide, potassium hydroxide, potassium carbonate, calcium hydroxide, ion exchange resins, deodorants, etc.
[0057] The functional material may be supported by impregnating the above-mentioned glass fiber sheet, glass fiber sheet molded body, or honeycomb molded body with a slurry containing the functional material, followed by drying.
[0058] As described above, the glass fiber sheet of the present embodiment is composed mainly of glass fiber and contains wood pulp and binder in a specific ratio, so that the strength of the sheet is maintained while flexibility is imparted. Therefore, the glass fiber sheet of the present embodiment has excellent shape conformability and excellent functional material carrying ability. Furthermore, the glass fiber sheet of the present embodiment can exhibit sufficient strength even after carrying a functional material. EXAMPLES
[0059] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0060] <Example 1> As the fiber component, 60 parts by mass of glass fiber (fiber diameter: 6 μm, fiber length: 6 mm), 40 parts by mass of wood pulp (NBKP) beaten to 500 CSF, and polyvinyl alcohol (Poval K-17U6, manufactured by Kuraray) as a binder were added in an amount of 16 parts by mass per 100 parts by mass of the fiber component, and a small amount of a dispersant and an antifoaming agent as auxiliary agents were added to water, which was then mixed, stirred, and dispersed to prepare a raw material slurry with a concentration of 0.2% by mass. A randomly arranged web was formed by a wet papermaking method, and acrylic emulsion was applied at 0.2 g / m 2 The mixture was spray-coated so as to obtain a single layer of glass fiber sheet. The basis weight of the obtained glass fiber sheet was measured according to JIS P8124, and it was found to be 44 g / m 2 It was.
[0061] <Example 2> A glass fiber sheet was obtained in the same manner as in Example 1, except that the glass fiber was 70 parts by mass and the wood pulp (NBKP) was 30 parts by mass.
[0062] <Example 3> Basis weight 30g / m 2 A glass fiber sheet was obtained in the same manner as in Example 1, except for changing the above.
[0063] <Comparative Example 1> A glass fiber sheet was obtained in the same manner as in Example 3, except that the glass fiber was 92 parts by mass and the wood pulp (NBKP) was 8 parts by mass.
[0064] <Comparative Example 2> A glass fiber-containing sheet (hereinafter included in the glass fiber sheet) was obtained in the same manner as in Example 1, except that the glass fiber was 45 parts by mass and the wood pulp (NBKP) was 55 parts by mass.
[0065] <Comparative Example 3> Basis weight 60g / m 2 A glass fiber sheet was obtained in the same manner as in Example 1, except for changing the above.
[0066] <Comparative Example 4> A glass fiber sheet was obtained in the same manner as in Example 1, except that polyvinyl alcohol was not added.
[0067] <Evaluation method> The obtained glass fiber sheet was subjected to the following evaluations, and the results are shown in Table 1.
[0068] (Strength of glass fiber sheet) The obtained glass fiber sheet was measured for tensile strength by a Tensilon type tensile tester (manufactured by ORIENTEC Co., Ltd.) in accordance with the method of JIS P 8113 to judge its tensile strength. ○: Strong ×: Weak
[0069] (Corrugated) The obtained glass fiber sheet was processed into a corrugated shape with a height of 1.4 mm and a pitch of 2.6 mm to form a core paper, and the core paper was adhered to a flat sheet liner made of the obtained glass fiber sheet with an inorganic adhesive to perform a corrugated processing. This was then rolled up to produce a cylindrical honeycomb molded body.
[0070] "Evaluation of shape conformity" When the glass fiber sheet was processed into a corrugated shape, the shape conformability was evaluated based on the following indexes. ◯: The waveform is well shaped and the wave shape is good. ×: The waveform is poorly formed.
[0071] (Dust Fall) The honeycomb portion of the obtained honeycomb formed body was touched with a finger, and powder falling off was evaluated based on the following criteria. Good: No paper dust on your fingers. ×: Paper dust sticks to fingers.
[0072] (Supporting functional materials) The honeycomb molded body was immersed for 30 minutes in an impregnation solution in which titanium oxide, a VOC adsorbent, was dispersed in water at a high concentration as a functional material. It was then fired to produce a filter substrate. The honeycomb portion of the filter substrate was touched with a finger, and the supportability of the functional material was evaluated using the following index. ○: No powder falling off, excellent support ×: Powder falls off, poor support
[0073] [Table 1]
[0074] As shown in Table 1, Examples 1 to 3 had excellent shape conformability of the glass fiber sheet, had sufficient strength even after firing, and did not fall off. In Comparative Example 1, the strength and shape conformability of the glass fiber sheet were insufficient, and powder falling occurred in the honeycomb molded body. In Comparative Example 2, the support of the functional material was insufficient. In Comparative Example 3, the shape conformability of the glass fiber sheet was insufficient. In Comparative Example 4, the strength of the glass fiber sheet was insufficient, and powder falling occurred in the honeycomb formed body.
Claims
1. A glass fiber sheet for a filter, which contains glass fiber as a main component, further contains wood pulp and a binder, and is formed by wet papermaking, The glass fiber sheet for a filter functions as a filter by carrying a functional material therein, 51 to 85 mass % of the total fiber content of the glass fiber sheet for filters is the glass fiber, The glass fiber sheet for filters contains 30 to 49% by mass of the wood pulp. The content of the binder is 1% by mass or more based on the total mass of the glass fiber sheet for filters, The glass fiber sheet for filters has a basis weight of 15 to 55 g / m 2 and glass fiber sheet for filters, which is for corrugating.
2. 2. The glass fiber sheet for filters according to claim 1, wherein the wood pulp has a beating degree of 300 to 750 CSF.
3. 3. The glass fiber sheet for filters according to claim 1, wherein the weighted average fiber diameter of the glass fibers is 4 to 10 μm.
4. The glass fiber sheet for filters according to any one of claims 1 to 3, wherein the content of the binder is 25 mass % or less based on the total mass of the glass fiber sheet for filters.
5. The glass fiber sheet for filters according to any one of claims 1 to 4, wherein the binder comprises polyvinyl alcohol.
Citation Information
Patent Citations
Composite and efficient oil-water-separation filter paper for hydraulic filter
CN105986512A
Shifting method for sheet material
JP1980058518A
Manufacture of ceramic formed body
JP1985033250A
Antimicrobial glass fiber sheet
JP2000282389A
Sheet produced by paper-making process
JP2006009197A